วาทกรรมคำสอนในกลอนลำชุด “ข้าวนาหว่านสารเคมี” ของวีระพงษ์ วงศ์ศิลป์ - ทิพนา, สันติ (วารสารพุทธปรัชญาวิวัฒน์, 2025)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาวาทกรรมคำสอนในกลอนลำชุดข้าวนาหว่านสารเคมีของ วีระพงษ์ วงศ์ศิลป์ เป็นงานวิจัยเชิงคุณภาพ โดยศึกษาเนื้อหาจากกลอนลำ 10  กลอนลำ ผลการวิจัยพบว่า 1) วาทกรรมคำสอนด้านพระพุทธศาสนา เช่น ละเว้นอบายมุข อย่าหลงในวัตถุสิ่งของ ปฏิบัติตามศีล 5 2) วาทกรรมคำสอนด้านการประหยัดไม่เน้นปัจจัยที่ไม่จำเป็นต่อชีวิต  3) วาทกรรมคำสอนด้านการสอนผู้หญิง เช่น การแต่งกายการดื่มของมึนเมา การศึกษาของผู้หญิง สอนให้รักนวลสงวนตัว 4) วาทกรรมคำสอนด้านการศึกษา เช่น การสร้างครูสอนคุณธรรม สอนให้เด็กมุ่งมั่นในการเรียน 5) วาทกรรมคำสอนด้านการอนุรักษ์วัฒนธรรมประเพณี เช่น อนุรักษ์และสืบทอดภาษาอีสาน การแต่งกาย 6) วาทกรรมคำสอนด้านอาหารการกิน สอนให้กินอาหารดั้งเดิม 7) วาทกรรมคำสอนด้านการโหยหาอดีต วิธีทำนาและชีวิตดั้งเดิม และด้านการพูดของคนอีสานที่ไพเราะงดงาม The purpose of this research paper is to study the discourse of teachings in the KlonLum Kao na wan sankame of Weerapong Wongsilp, which is a qualitative research by studying the content of 10 poems The research results found that 1)Buddhist teaching discourse, such as ignoring abysmal, do not be lost in objects, followed the sacraments 5. 2) Economical doctrinal discourse. 3) Women's teaching discourse such as dress, drinking of intoxication, women's education, teaching to love reserved 4) Educational discourse such as creating morality teachers, teaching children to commit to learning, 5) Traditional cultural preservation teachings such as preserving and inheriting Isaan languages, dress code 6) Food teaching discourse, teaching traditional food, teaching to eat traditional foods, 7) Yearning teaching discourse on the past. Farming and traditional life the speaking side of the beautiful Isaan people.